Meningkatkan Keterampilan Membuat Celengan Batok Kelapa Melalui Metode Explicit Instruction Berbasis Analisis Tugas bagi Peserta Didik Tunagrahita Ringan di Kelas VIII SLB Ummi Khaira - Anisa, Anisa; Z, Martias (Jurnal Penelitian Pendidikan Khusus, 2021)
The purpose of this study is to find out how the process of improving the skill of making coconut shell piggy bank through explicit instruction method based on task analysis for students with mild retardation. The research method used is meode class action research with qualitative approach. The subjects in this study were the learning of mild retardation students learners. Technical data analysis used is to perform data collection, data reduction and conclusion withdrawal. This research is conducted with two cycles, each cycle consists of planning, execution of actions, observations and reflections. The results obtained in the first cycle is that the value of each student has increased but has not reached the kkm limit while the results obtained in cycle two, the value of learners has increased and has reached the kkm limit. conclusion of the skill of making coconut shell piggy bank experienced a significant improvement through explicit instruction method based on task analysis.